Open- and Closed-Label Placebo and Nocebo Suggestions About a Sham Transdermal Patch - Meeuwis, Stefanie H. (Psychosom Med, 2021)
OBJECTIVE: Placebo effects may occur when it is known that an inert substance is given (i.e., open-label placebo). It is not yet clear whether these effects are similar to concealed (i.e., closed-label) placebo effects for itch or whether nocebo effects can be induced under open-label conditions. METHODS: Healthy volunteers (n = 112) were randomized to an open-label (I) or closed-label (II) positive suggestions group, or an open-label (III) or closed-label (IV) negative suggestions group. Participants were told, as cover story, that a transdermal caffeine patch would be applied that positively influences cognitive abilities and, as a side effect, positively or negatively (depending on group allocation) influences itch. Participants in the open-label groups were given a rationale explaining placebo and nocebo effect mechanisms. Itch (the primary outcome) was induced at baseline and postsuggestions by histamine iontophoresis. RESULTS: Analyses of variance revealed significantly lower itch in the positive compared with the negative suggestions groups for both open- and closed-label contexts (all, p ≤ .008, Cohen d ≥ 0.47). Self-rated skin response was less severe after positive versus negative suggestions (all, p ≤ .017, Cohen d ≥ 0.33), but no effects on physical skin response were found (all, p ≥ .23, Cohen d ≤ 0.30). CONCLUSIONS: Itch can be reduced by positive compared with negative suggestions under both open- and closed-label conditions. These findings indicate that open-label suggestions may potentially be a tool to use placebo effects for self-reported outcomes in clinical practice, for example, by explaining the role of expectancy in treatment. It needs to be investigated further under which circumstances an open-label rationale may impact placebo and nocebo effects. Trial Registration: www.trialregister.nl; NTR7174